SALTING-OUT EFFECT OF SINGLE SALTS Na2SO4 AND NaNO3 ON THE LLE OF THE SYSTEMS (WATER + TOLUENE + ACETONE), (WATER + CYCLOHEXANE + ETHANOL OR 2-PROPANOL) AND (WATER + XYLENE + METHANOL) - LAIADI, DJEMOUI; HASSEINE, ABDEL MALEK; MERZOUGUI, ABDELKRIM; ABABSA, ASMA (Courrier du Savoir, 2018)
The effect of sodium nitrate and sodium sulphate on the distribution of acetone, ethanol, methanol and 2-propanol between toluene, Cyclohexane, xylene and water at 25°C has been experimentally investigated. The McDevit and Long method has been employed to correlate the tie line data. Compared with previous work, the order of decreasing salting out, on a weight basis, is: Na 2 SO 4 > NaCl >KCl > NaNO 3       for water + toluene + acetone Na 2 SO 4 > NaCl > NaNO 3 > KCl     for water + cyclohexane or xylene+ alcohol